Influencing factors and consumer purchase intention through online platform in Malaysia cosmetics industry - Hoo, Wong Chee; Quinn, Irene Toh Ee; Wolor, Christian Wiradendi; Annamalah, Sanmugam; Ven, Chan Pee (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of social media marketing on consumer purchase intentions within Malaysia’s cosmetics industry. It focuses on four key independent variables: social media advertising, brand familiarity, influencer credibility, and the trustworthiness of social media platforms. Through a quantitative research approach, data were collected from 385 social media users using a structured survey. The findings reveal that all four factors significantly influence purchase intentions, with influencer credibility demonstrating the strongest impact. These results highlight the importance of strategic social media marketing in shaping consumer behavior, emphasizing the need for targeted advertising, brand engagement, credible influencers, and trustworthy platforms. The research provides actionable insights for cosmetic brands aiming to enhance their digital marketing strategies. By addressing the dynamics of consumer trust, advertising effectiveness, and brand familiarity, the study offers practical recommendations to drive purchase intentions in an increasingly competitive digital marketplace. This work contributes to the academic understanding of social media marketing and offers a robust framework for future studies in the cosmetics and broader digital marketing sectors.